BOLD quantified renal pO2 is sensitive to pharmacological challenges in rats. Issue 1 (8th August 2016) - Thacker, Jon; Zhang, Jeff L.; Franklin, Tammy; Prasad, Pottumarthi
Abstract : Purpose: Blood oxygen level‐dependent (BOLD) MRI has been effectively used to monitor changes in renal oxygenation. However, R2* (or T2*) is not specific to blood oxygenation and is dependent on other factors. This study investigates the use of a statistical model that takes these factors into account and maps BOLD MRI measurements to blood pO2. Methods: Spin echo and gradient echo images were obtained in six Sprague‐Dawley rats and R2 and R2* maps were computed. Measurements were made at baseline, post‐nitric oxide synthase inhibitor (L‐NAME), and post‐furosemide administration. A simulation of each region was performed to map R2′ (computed as R2*–R2) to blood pO2. Results: At baseline, blood pO2 in the outer medulla was 30.5 ± 1.2 mmHg and 51.9 ± 5.2 mmHg in the cortex, in agreement with previous invasive studies. Blood pO2 was found to decrease within the outer medulla following L‐NAME ( P  < 0.05) and increase after furosemide ( P  < 0.05). Blood pO2 in the cortex increased following furosemide ( P  < 0.05). Conclusions: Model‐derived blood pO2 is sensitive to pharmacological challenges, and baseline pO2 is comparable to literature values. Reporting pO2 instead of R2* could lead to a greater clinical impact of renal BOLD MRI and facilitate the identification of hypoxic regions. Magn Reson Med 78:297–302, 2017. © 2016 International Society for Magnetic Resonance in Medicine